CLA's most outstanding faculty - Quito, Enerita S. (Animo Repository, 1993)
Dr. Emerita S. Quito was awarded CLA's Most Outstanding faculty during the College of Liberal Arts Week celebration. Dr. Quito delivered her response, Teaching as an Art.